Molecular Dynamics and Therapeutic Architectures of Cannabinoid Receptors: A Comprehensive Review - R. Madhumitha Sri*; R.M. Aadarshvel; S. Ravichandran (International Journal of Cheminformatics, 2026)
Expanding on these foundations, recent structural biology studies using cryo-electron microscopy have provided high-resolution insights into the conformational dynamics of CB₁ and CB₂ receptors. These findings have enabled a more precise understanding of ligand–receptor interactions, particularly how agonists, antagonists, and reverse agonists stabilize distinct receptor states. Such knowledge is critical for rational drug design, allowing researchers to selectively modulate downstream signaling pathways. For instance, CB₁ receptors primarily couple to Gi/o proteins, leading to inhibition of adenylate cyclase, reduced cAMP levels, and modulation of ion channels, whereas CB₂ activation influences immune cell migration and cytokine release. In addition, the therapeutic landscape has shifted toward peripherally restricted CB₁ modulators to avoid central nervous system side effects such as anxiety and depression, which were observed with earlier compounds like rimonabant. Advances in nanotechnology-based drug delivery systems have further improved the bioavailability and targeting precision of cannabinoid-based therapeutics. Moreover, the integration of artificial intelligence in drug discovery pipelines has accelerated the identification of novel cannabinoid ligands with improved safety profiles. Collectively, these developments underscore the growing potential of ECS-targeted therapies in precision medicine, particularly for conditions with limited treatment options.
Keywords: CB₁ receptors; Cannabinoid; G-protein signaling; cryo-electron microscopy; β-arrestin